Prospective, randomized, controlled study of the efficacy of transcatheter arterial chemoembolization with miriplatin for hepatocellular carcinoma. Issue 3 (30th July 2017) - Kubota, Kousuke; Hidaka, Hisashi; Nakazawa, Takahide; Okuwaki, Yusuke; Yamane, Keiko; Inoue, Tomoyoshi; Uojima, Haruki; Takada, Juichi; Tanaka, Yoshiaki; Shibuya, Akitaka; Fujii, Kaoru; Woodhams, Reiko; et al.
Abstract : Aim: Transcatheter arterial chemoembolization (TACE) has been recognized as a treatment option for patients with intermediate hepatocellular carcinoma (HCC). This randomized, controlled study compared the local control efficacy of TACE with miriplatin (platinum monohydrate) or with epirubicin. Methods: The study group consisted of 200 Japanese patients with unresectable HCC treated at the Kitasato University East Hospital (Sagamihara, Japan) between July 2010 and June 2013. The primary end‐point of the study was time to tumor progression (TTP). Results: We analyzed 198 patients (99 in the miriplatin group and 99 in the epirubicin group) treated with TACE. The median TTP in the epirubicin group was 5.9 months (95% confidence interval [CI], 4.8–7.0) and 7.6 months (95% CI, 5.8–9.4) in the miriplatin group. There was a significant difference between the two groups ( P  = 0.021; risk ratio, 1.488; 95% CI: 1.061–2.086). In the epirubicin group, 53 patients (53%) had complete response, 24 patients (24%) had partial response, 12 patients (12%) had stable disease, and 10 patients (10%) had progressive disease. In the miriplatin group, 38 patients (38%) had complete response, 41 patients (41%) had partial response, 2 patients (2%) had stable disease, and 18 patients (18%) had progressive disease. There was no significant difference in the response rate ( P  = 0.862). Overall incidences of adverse events and adverse drug reactions did not differ significantly between the two groups. Conclusion: Miriplatin proved more effective than epirubicin in TACE for unresectable HCC. The trial described in this work has been registered under the trial number: UMIN000004790.